Ceramic Sensors: A mini-review of their applications - Krishna Prasad, N. V.; Venkata Prasad, K.; Ramesh, S.; Phanidhar, S. V.; Venkata Ratnam, K.; Janardhan, S.; Manjunatha, H.; Sarma, M. S. S. R. K. N.; Srinivas, K. (Frontiers in Materials, 2020)
We are living in a sensor world. Sensors are used in the house, office, car, and other areas detecting our presence by turning lights on, adjusting room temperature, detecting fires, and many other tasks. Today sensor has become a “buzz word”, without which it is hard to imagine living. They play a vital role in all sectors including housing, industry, aviation, medicine, and automobiles to name a few. Sensors can be manufactured with many types of materials. However, sensors made of ceramics have significance and have advantages when compared to those made from other materials. This mini review examines ceramic sensors and their applications in various sectors including the materials used to build them and their functioning in different areas. The paper precisely reports ceramic sensors and their applications in industry, including the medical, automotive, and aviation sectors.